A65 SYSTEMATIC REVIEW OF PROGNOSTIC SCORES FOR RECURRENCE OF HEPATOCELLULAR CARCINOMA AFTER LIVER TRANSPLANTATION. (15th March 2019) - Aziz, S; Teriaky, A; Qumosani, K
Abstract: Background: Recurrence of hepatocellular carcinoma (HCC) after liver transplantation is a major cause of morbidity and mortality. Several risk assessment tools have been developed, although to date, there is no widely accepted tool to predict HCC recurrence. Aims: The aim of the current study was to critically appraise published literature on clinicopathologic prognostic scoring systems assessing recurrence of HCC after transplantation. Methods: An electronic data base search was performed using MEDLINE, EMBASE, Cochrane library, and Central Registry of Clinical Trials. All retrospective chart reviews and validation studies that analyzed prognostic scoring systems consisting of clinical and explant pathologic characteristics to determine recurrence risk of hepatocellular carcinoma post-transplant between 2000–2017 were included. Results: The literature search identified 145 studies, of which 134 were excluded. From the 11 scoring systems, 6 had been validated. 7 out of the 11 assigned weight to the presence of microvascular invasion. All studies included tumor diameter in their respective scoring systems. Conclusions: Several scoring systems exist to classify risk of HCC recurrence post-transplant. Head to head comparison study would be beneficial in identifying which prognostic score has the best predictive ability. Funding Agencies: None